Greenhouse gas implications of replacing fish protein with beef in the lower Mekong Basin. (7th April 2020) - Galea, Ben; Pittock, Jamie; Crimp, Steven
Abstract : At least 88 new hydropower dams are planned between 2010 and 2030 in the lower Mekong River basin in Southeast Asia as a source of electricity with lower greenhouse gas emissions. Dams result in declines in fish populations that will need to be replaced with other sources of protein for food security. We make the first assessment of emissions should beef production substitute for lost fish in Cambodia and Laos. We assessed two sources of emissions. Replacing lost fish with beef would require as much as 12 million hectares of new pasture. Forest clearing for pastures in Cambodia and Lao PDR would initially emit between 0.859 and 3.015 giga‐tonnes of carbon dioxide equivalents (Gt CO2 ‐eq.). Methane emissions from additional cattle would add at least 0.0013 Gt CO2 ‐eq./year to Cambodia's total greenhouse gas emissions, equivalent to a 20% increase. In Laos at least 0.0005 Gt CO2 ‐eq./year would be released, a 4–12% increase in annual emissions. We demonstrate that activities displaced by hydropower developments could significantly increase emissions. It shows how enclosure of commons at local scales impacts upon other common pool resources at different scales, raising questions for sustainable and equitable transboundary governance.